An Outbreak of Foodborne Botulism in Ontario - Mona R Loutfy; John W Austin; Burke Blanchfield; Ignatius W Fong (Canadian Journal of Infectious Diseases)
Botulism is a rare paralytic illness resulting from a potent neurotoxin produced by Clostridium botulinum. Botulism in Canada is predominately due to C botulinum type E and affects mainly the First Nations and Inuit populations. The most recent outbreak of botulism in Ontario was in Ottawa in 1991 and was caused by C botulinum type A. We report an outbreak of foodborne type B botulism in Ontario, which implicated home-canned tomatoes. The outbreak was characterized by mild symptoms in two cases and moderately severe illness in one case. The investigation shows the importance of considering the diagnosis of botulism in patients presenting with cranial nerve and autonomic dysfunction, especially when combined with gastrointestinal complaints; it also highlights the importance of proper home canning technique.